Strategi Retorika Digital Host YouTube MotoMobi dalam Membangun Kredibilitas Reviu Otomotif - Khalil, Muhammad Ibrahim; Purwanti, Silviana (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The rapid growth of YouTube has transformed automotive review content into one of the primary sources of consumer information. In this context, reviewers' credibility is shaped not only by technical knowledge but also by effective rhetorical communication. This study aims to analyze the digital rhetorical strategies employed by the host of the MotoMobi YouTube channel in constructing credibility through verbal and nonverbal communication. This research adopted a qualitative content analysis approach by examining five MotoMobi videos with the highest number of views published between June and October 2025. Data were collected through observation, documentation, and note-taking techniques and analyzed using Aristotle's rhetorical framework consisting of ethos, pathos, and logos. The findings reveal that credibility is constructed through the integration of verbal rhetoric, including clear diction, storytelling, humor, hyperbolic expressions, and the recurring slogan Kami Suka Turbo, with nonverbal rhetoric manifested through consistent visual identity, expressive gestures, dynamic vocal intonation, eye contact, and direct interaction with reviewed vehicles. The integration of these rhetorical elements strengthens persuasive communication, enhances audience engagement, and establishes MotoMobi as a credible automotive reviewer within Indonesia's digital media ecosystem.